Fragmented narrative: telling and interpreting stories in the Twitter age - Sadler, Neil (Routledge, Taylor & Francis Group, 2022)
Acknowledgements Introduction Chapter One -- Theorising fragmented narrative: Knowing and being Chapter Two -- Telling stories with fragments: Vertical, horizontal and ambient narrative Chapter Three -- Interpreting fragmented stories I: Open texts, distanciation and writerly readers Chapter Four -- Interpreting fragmented stories II: Existential understanding, limited horizons and narrative forestructuring Chapter Five -- Narrative and truth: Correspondence, coherence and disclosure Conclusion -- Stories, Citizens and Being Glossary of Heideggerian terms Bibliography Index
https://katalog.fid-bbi.de/Record/183-1767900708